The Influence of Halal Certification and Product Quality on Interest in Purchasing Wardah Cosmetic Products at The Raudlotul Muttaqin Islamic Boarding School - Bintii Kholifatun Nisa; Syuhada' Syuhada'; Ahmad Munir Hamid (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
This study examines the influence of halal certification and product quality on interest in buying Wardah cosmetic products at the Raudlotul Muttaqin Islamic Boarding School, Talun Sidogembul Sukodadi, Lamongan. The study was conducted using a quantitative approach and using a survey method. Data obtained through the distribution of questionnaires using a Google form which was processed and analyzed using the SPSS tool. The population in this study refers to all consumers who use Wardah cosmetic products at the Raudlotul Muttaqin Islamic Boarding School. The sample used in this study amounted to 30 respondents who were consumers of Wardah cosmetic products. The results of the study show that: 1) Halal certification has a positive and significant effect on interest in buying Wardah cosmetic products, this was obtained from the T test, where the calculated t of 3.011 is greater than the t table of 2.051 or the significance value of the t test is 0.006 less than 0.05 (a = 5%).and product quality significantly influences consumer interest in buying Wardah cosmetic products at the Raudlotul Muttaqin Islamic Boarding School. 2) Product Quality has a positive and significant effect on the interest in buying Wardah cosmetic products. This is obtained from the T test, where the calculated t of 9.464 is greater than the t table of 2.051 or the significance value of the t test of 0.006 is smaller than 0.05 (a = 5%). 3) Halal Certification and Product Quality have a positive and significant effect on the interest in buying Wardah cosmetic products. This is obtained from the results of the F test which shows the results of the F test value of 52.838 with a significance value of 0.000, thus it can be seen that the calculated f is greater than the f table, namely 52.838> 3.34 with a significance value of 0.000 <0.05.